Living on the slope. The Middle and Upper Paleolithic occupation of Feldberg “Steinacker” Leben auf dem Hang. Die mittel- und jungpaläolithische Besiedlung von Feldberg „Steinacker” - Bradtmöller, Marcel; Bubenzer, Olaf; Hecht, Stefan; Tschocke, Diethard; Calvo, Aitor; Fernández, Arantzazu Jindriska Pérez; Schmidt, Christoph; Marreiros, Joao; Henselowsky, Felix; Hattermann, Merlin-Janis; Bauer, Lisa; El-Kassem, Marcel (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2022)
This article is dedicated to the Paleolithic open-air site of Feldberg “Steinacker”, located between the Rhine and the Black Forest near Freiburg/Breisgau in South-West Germany. The site was discovered by W. Mähling in 1969 and is primarily known for the presence of tanged points (Font-Robert type), as well as a possible connection via raw material transport to the cave sites of the Swabian Jura. However, stratigraphic context, site formation processes and site function remained unclear. In 2018, the Heritage Management of Baden-Wuerttemberg and the University of Rostock began the first scientific investigations at the site. It was possible to document a knapping area from the Gravettian, presumably in situ. The excavations also revealed a Middle Paleolithic occupation, making “Steinacker” for the moment the only open-air site in South-West Germany where a stratification of Middle to Upper Paleolithic is present. The investigations were accompanied by additional analyses related to site-formation processes and artefact morphology. Geomagnetic and geoelectric prospection as well as sedimentological drilling revealed a complex paleo-relief that was very different from the current topography. Micromorphology and optically stimulated luminescence dating confirmed that the excavated archaeological stratigraphy was largely intact. Moreover, use-wear analysis showed that pieces with strong indications of frost alterations were possibly used on a regular basis at the site.
CRIS-Team Scopus Importer:2024-12-16
Keywords: ERT Survey; Geomagnetic Survey; Gravettian; Mousterian; open-air site; site-formation processes; use-wear analysis

LOST IN THE QUEST FOR FLINT: A GRAVETTIAN HUNTING CAMP (USATEGI, BASQUE COUNTRY) - Calvo, Aitor; Arrizabalaga, Alvaro (Oxford Journal of Archaeology, 2021)
Five decades ago, Usategi Cave (Basque Country) yielded a small Gravettian series that included an Isturitz-type bone point. This paper presents the first 14C dates for the assemblage and new data obtained by the study of the lithic raw materials, a high proportion of which came from north of the Pyrenees. The discussion of this new information leads to the hypothesis that the occupants of the cave were a group that travelled from the continental Basque Country across the Pyrenean mountain passes and the Ebro basin to procure flint from the nearest outcrop at Urbasa.
CRIS-Team Scopus Importer:2021-10-08

Piecing together a new mosaic: Gravettian lithic resources and economic territories in the Western Pyrenees - Calvo, Aitor; Arrizabalaga, Alvaro (Archaeological and Anthropological Sciences, 2020)
To palliate the current scarcity of information about lithic raw materials in the Western Pyrenees during the Gravettian, the study of ten assemblages has explored the flint procurement patterns and economic organisation of the territory. The study was based on the macro- and microscopic analysis of the different lithic remains. A wide range of flint varieties were used, including some excellent rocks for knapping and others of poorer quality. This diversified catchment pattern was defined by the criteria of quality and suitability for reduction. Although procurement took place mostly at the primary outcrops, there is some evidence of limited acquisition in secondary deposits. Within the economic territory of the Western Pyrenees, divergences in the connections between the outcrops on one side of the mountains and the archaeological sites on the other may indicate different territorial or economic roles for each side. In general terms, the northern side may have been more residential with more stable habitation, while the southern side was linked with logistic tasks and more seasonal occupation. The economic connections between this territory and surrounding areas revealed by the lithic resources are the reflection of inter-group contacts and an economic mosaic imbricated with a cultural or symbolic one.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Economy; Gravettian; Lithic industry; Raw materials; Territory; Upper Palaeolithic